Outcomes following surgical management of inguinal-related groin pain in athletes: a case series. Issue 1 (22nd January 2020) - Gerhardt, Michael; Christiansen, Josh; Sherman, Benjamin; Miranda, Alejandro; Hutchinson, William; Chahla, Jorge
Abstract: To determine the outcomes of a limited surgical intervention, consisting of neurolysis, inguinal wall repair and/or adductor debridement of adhesions based on intraoperative findings. Retrospective case series. Outpatient orthopedic/general surgery clinic. Fifty-one athletes treated surgically for inguinal-related groin pain from 2009 to 2015. Limited surgical intervention, consisting of neurolysis, inguinal wall repair and/or adductor debridement based on intra-operative findings. Ability to return to sport at the same level, time to return to play. Fifty-one athletes were included in the study with an average follow-up of 4.42 years (range 2.02–7.01). The average age was 24.2 years (range 16–49) and consisted of 94.0% males and 6.0% females. Nerve entrapment was demonstrated in 96.2% of cases with involvement of the ilioinguinal in 92.5%, the iliohypogastric in 30.8% and the genitofemoral in 13.2%. Attenuation of the posterior inguinal wall was present and repaired in 79.3% of cases. Scar tissue was present around the adductor origin and required debridement in 56.7% of cases. Forty-nine (96.1%) athletes returned to sport at the same level of play at an average of 5.9 weeks. Two athletes required a revision surgery. High rates of return to sport were achieved after surgery for inguinal-related groin pain that addresses the varying pathology and associated nerve entrapment.